The Effect of Student Sharia Financial Literacy on Student Financial Behavior (Case Study of Islamic Economics Students - Alfina Audia Sabastio (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
Behavioral finance is a field of science that combines behavioral and cognitive psychological theory with conventional economics and finance that is useful for explaining why people make irrational financial decisions. Financial literacy is related to everyday life. As in making decisions to save, both short-term and long-term financial decisions. This is the role of literacy in everyday life. Therefore, financial intelligence is the main thing that must be considered in everyday life. The purpose of this study was to determine the effect of Islamic financial literacy on student financial management behavior. The object of this research is 100 students of Islamic Economics at Diponegoro University. Data was collected using a questionnaire which was then processed and analyzed using a simple linear regression method. From the data processing, it is obtained that Islamic financial literacy with dimensions of subjective knowledge about sharia compliance, subjective knowledge of usury and profit sharing on Islamic finance has a significant positive effect on financial behavior with the dimensions of saving behavior, spending behavior, long-term financial behavior, short- term financial behavior.